2023
DOI: 10.1038/s41398-023-02483-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of microtubule actin crosslinking factor 1 (MACF1) in bipolar disorder pathophysiology and potential in lithium therapeutic mechanism

Abstract: Bipolar affective disorder (BPAD) are life-long disorders that account for significant morbidity in afflicted patients. The etiology of BPAD is complex, combining genetic and environmental factors to increase the risk of disease. Genetic studies have pointed toward cytoskeletal dysfunction as a potential molecular mechanism through which BPAD may arise and have implicated proteins that regulate the cytoskeleton as risk factors. Microtubule actin crosslinking factor 1 (MACF1) is a giant cytoskeletal crosslinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 124 publications
(168 reference statements)
0
1
0
Order By: Relevance
“…This suggests that the SH3 interactions with the PRPs characterized in this study go beyond SOS1 as a binding partner, although the binding specificities of the listed proteins (Figure 4) remain to be investigated. However, several studies confirm the interactions of the identified proteins with SH3DCPs, including zinc finger proteins with p130Cas [28], MACF1 with Spectrin [29], DLGAP with DLG [30], WRCH1/RHOU with GRB2 [31,32], Paxillin with SRC [33,34], and SSTR5 with Homer, Dynamin, IRSp53, and Cortactin [35].…”
Section: Sh3 Domain-prp Relationships Beyond Sos1mentioning
confidence: 93%
“…This suggests that the SH3 interactions with the PRPs characterized in this study go beyond SOS1 as a binding partner, although the binding specificities of the listed proteins (Figure 4) remain to be investigated. However, several studies confirm the interactions of the identified proteins with SH3DCPs, including zinc finger proteins with p130Cas [28], MACF1 with Spectrin [29], DLGAP with DLG [30], WRCH1/RHOU with GRB2 [31,32], Paxillin with SRC [33,34], and SSTR5 with Homer, Dynamin, IRSp53, and Cortactin [35].…”
Section: Sh3 Domain-prp Relationships Beyond Sos1mentioning
confidence: 93%